Workers' culture in imperial Germany : leisure and recreation in the Rhineland and Westphalia - Abrams, Lynn (Routledge, 1992)
This new book represents the first alternative approach to the study of workers' culture in Imperial Germany. It also provides the first comprehensive historical analysis of the emergence of Germany's modern leisure industry. Lynn Abrams offers a unique insight into the German working class. She examines the emergence of a distinct workers' culture, focusing on the popular festivals of the early industrial years and the mass, commercial culture epitomized by the cinema. Workers' Culture in Imperial Germany will appeal to the specialist student of Imperial Germany, particularly in the areas of German social and cultural history. It will also be useful for undergraduate courses on modern German history and for historians of European leisure and culture. Workers' Culture in Imperial Germany focuses on the leisure activities enjoyed by workers in the major cities of Bochum and Dusseldorf. It covers a whole range of popular amusements and recreations on offer including festivals, pubs, Tingel-Tangels, dance halls, clubs and cinema. The book contributes to the debate over the role of a working-class culture in Imperial Germany.